ASPEK HUKUM PERLINDUNGAN PELAKU TINDAK PIDANA PEMBUNUHAN DALAM HUKUM POSITIF DAN PERSPEKTIF KUHAP - Muhammad Ubet Al Asad (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACTLegal protection can be interpreted as all the efforts of the government to ensure legal certainty to provide protection to its citizens so that their rights as citizens are not violated, and imposed sanctions for someone who violates these regulations in accordance with applicable regulations, and will have consequences especially in the law criminal .. Talking about legal protection is certainly very closely related to Human Rights (HAM). Legal protection is all efforts to fulfill rights and provide assistance to provide security for witnesses and/or victims, legal protection for victims of crime as part of community protection can be realized in various forms, such as through the provision of restitution, compensation, medical services, and legal assistance.How is the Protection of Murderers in Positive Law and Criminal Procedure Codehow the Protection of Murderers in Criminal Procedure Perspectives The type of research used in this study is normative legal research, which is a legal research method that uses a statutory approachThe regulation of human rights in Indonesia has gained a place in the constitution, namely in Chapter X.A, the 1945 Constitution of the Republic of Indonesia, starting from Article 28A to Article 28J. Rights accompanied by a Legal Counsel include conditions for human rights values, these rights are protected by law, especially Law Number 39 of 1999 concerning Human Rights, and Law Number 4 of 2004 concerning Judicial Power and the existence of rights accompanied by an Advisor The law has been universally recognized as part of human rights. Keywords: Legal Protection, Murderer, Criminal Procedure Code